Mass-spectra of Evaporation of Glasses in As-S System - Valentyn Ivanitsky; Victor Kovtunenko; Roman Meshko; Myhajlo Ryaboschuk; Stoika Myroslav; Валентин Іваницький; Віктор Ковтуненко; Роман Мешко; Михайло Рябощук; Стойка Мирослав; Sztojka Miroszláv (Society for Cultural and Scientific Progress in Central and Eastern Europe, 2017)
Abstract. The mass-spectra of six different compositions of As-S glasses under thermal evaporation from Knudsen cell within the temperature range of 400 - 520 K have been studied. The complicated complex nature of vapour flows of these glasses which contain about three tens of different AsmSn atomic complexes (m = 0 - 4 , n = 0 - 8 ) has been revealed. By increasing the flow density of an ionizing electron beam of the mass-spectrometer the coincidence of the total mass-spectrometric composition of the vapour phase with the chemical composition of glasses before evaporation has been ensured. The presence of three types of concentration dependences for different AsmSn clusters versus the chemical composition of initial glasses: growing, decreasing, dome-shaped ones has been established. The influence of technological conditions of synthesis for As-S glasses on their mass-spectra has been revealed.
Keywords: mass-spectrometry; arsenic-sulfur clusters; evaporation of chalcogenides; мас-спектрометрія; миш'яково-сірчані кластери; випаровування халькогенідів; tömegspektrometria; arzén-kén klaszterek; kalkogenidek elpárologtatása